Das "Nydamboot" im Museum: Inwertsetzungen und Präsentationen im Wandel der Zeit - Schade, Tobias (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
value, however, is not inherent but culturally constructed and is closely related to practices of valorisation. These objects, and also the past itself, may become socio-cultural ›resources‹ (according to the definition of the Collaborative Research Centre SFB 1070 ResourceCultures). As such they have meanings for museums, societies, and social groups. These meanings can also become evident in the way the objects are presented in museums, in the changing presentations through time, and in the way they are received. The focus of this article is the process of musealisation and on exhibition studies using the example of the ›Nydamboot‹ exhibited in Schleswig (Germany). Based on various sources from archives and newspapers as well as interviews with experts, this contribution discusses how the archaeological find in the bog became the present exhibit ›Nydamboot‹, and how meanings related to the boat changed through time and became apparent in its exhibitions in Flensburg, Kiel, and Schleswig: the ›Nydamboot‹ is not only an archaeological object or an exhibit, it is also a historical witness, a creator of identity, and a symbol.